Hidrotalcitas multimetálicas para produção de gás de síntese a partir do biogás - Lino, Ananda Vallezi Paladino (2015)
In this work, catalysts derived from hydrotalcites were employed in Direct Reforming of Biogas, once they feature the necessary basicity to allow and improve carbon removal during reforming. As a differential study, the effect of the step ageing elimination during hydrotalcites syntheses, which were prepared by means of coprecipitation technique, was also evaluated. The results obtained from temperature effect evaluation tests ranging from 800 to 500oC suggested there was no need of precursors ageing, which represents an energy saving during catalysts syntheses, once this step represents the most energy expensive. To improve the process and reduce carbon deposition, oxygen was added as synthetic air into the gaseous reactants feed, in a reaction known as Oxidative Reforming of Biogas. In this case, the ratio H2/CO was close to 1, along the temperature range from 800 to 500oC considered during the catalytic tests, which was assigned to the occurrence of methane partial oxidation, specially in lower temperatures. As an attempt to improve carbon gasification during reforming reactions, element cerium was also added during the syntheses of hydrotalcites, also by coprecipitation, fixing the amount of this element and ranging nickel amount, eliminating the step ageing. At this point, cerium promoted and unpromoted catalysts were compared through biogas direct reforming 6 hours stability tests at 650oC. The spent catalysts were characterized by thermogravimetric analysis in order to evaluate the amount of carbon deposited over the catalyst surface. It was found for the catalysts derived from oxides corresponding to 5 and 15% of nickel (% nominal, in weight) a higher carbon deposition at the presence of cerium promoted catalysts, although for the first one, the carbon temperature peak removal was lower than unpromoted catalyst. On the contrary, for the catalysts corresponding to 10 and 25% of nickel (% nominal, in weight), similar and lower carbon deposition was found in presence of cerium. It was also possible to confirm the reduction of carbon deposition after stability tests for oxidative reforming of biogas, compared to the direct reforming.